2(r-3)=0

Simple and best practice solution for 2(r-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(r-3)=0 equation:


Simplifying
2(r + -3) = 0

Reorder the terms:
2(-3 + r) = 0
(-3 * 2 + r * 2) = 0
(-6 + 2r) = 0

Solving
-6 + 2r = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 2r = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 2r = 0 + 6
2r = 0 + 6

Combine like terms: 0 + 6 = 6
2r = 6

Divide each side by '2'.
r = 3

Simplifying
r = 3

See similar equations:

| 6x+2y=18 | | 6x+4=3x+28 | | y+(-4)=9 | | 14-7(x+1)=3x-9 | | -am*am*3m= | | x=309-d | | 23y-500=73y-100 | | 3k-17=4 | | 15ab-32ab^2= | | -6p+11=2p-13 | | 2(2f+4)=4(f+2) | | 1-2(3a-5)=3(-2a+1)+8 | | 16t^2-484=0 | | 12x+8=7x+2 | | x+6=6x-66 | | 16y+2x=18 | | -7(-3x-6)=84 | | 16x+2y=18 | | 4x-5-2x= | | .5(y+6)-3=8 | | 0.3-15=0.2x-5 | | -4m+5=-2m-15 | | 2x+7=39-6x | | (4-1)m-m=(m-1)8*4 | | s=15p | | 2x+5=41-x | | 3(6x-1)-2(x+3)=8(x+1) | | 2x+8y-26=0 | | 3(x^2-x)=3x^2+5x-11 | | (8x-10)+(6X)+(10x+10)= | | 7(u+2)=4u+35 | | 4x+2=7x-9 |

Equations solver categories